2021
DOI: 10.1111/1756-185x.14057
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps and inflammatory response: Implications for the immunopathogenesis of ankylosing spondylitis

Abstract: Aim Ankylosing spondylitis (AS) pathogenesis has focused on the adaptive immune response; however, innate immune responses may also play a role in the inflammatory response of AS. Dysregulated neutrophil activation can induce tissue damage and contribute to the pathogenesis of immune‐related diseases. Hence, the aim of this study was to assess the effect of immune complexes formed with the p30 of Salmonella typhimurium and anti‐p30 antibodies present in the sera of AS patients and controls in inducing the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Moreover, our findings suggest a reciprocal causation between TRAIL and AS. In AS, IL-1β is also considered a critical pro-inflammatory cytokine, and its expression levels may be upregulated, similar to findings by Zambrano-Zaragoza and Peng ( 32 , 33 ), who observed elevated IL-1β levels in AS patients. However, this does not necessarily imply that IL-1β can cause AS; it could also be a negative feedback regulation by the body to protect itself.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, our findings suggest a reciprocal causation between TRAIL and AS. In AS, IL-1β is also considered a critical pro-inflammatory cytokine, and its expression levels may be upregulated, similar to findings by Zambrano-Zaragoza and Peng ( 32 , 33 ), who observed elevated IL-1β levels in AS patients. However, this does not necessarily imply that IL-1β can cause AS; it could also be a negative feedback regulation by the body to protect itself.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, it can serve as a marker for systemic rheumatism, as indicated by recent research. [38][39][40] Meacan et al [41] found that an increase in neutrophil count is generally associated with poor prognosis and increased mortality. A clinical metaanalysis study also showed that NLR is a reasonable measure for detecting systemic inflammation in AS patients and can indicate disease activity in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…NETs can act as an autoantigen to coordinate congenital and adaptive immune disorders, participate in the self-magnifying cycle of autoimmune inflammation, and produce cell and tissue-specific damage in autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus (Fousert et al, 2020;Goel and Kaplan, 2020). Similarly, NETs production increased in AS and was associated with AS inflammation and activity (Ruiz-Limon et al, 2018;Zambrano-Zaragoza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%